2009
DOI: 10.1080/00016480802454724
|View full text |Cite
|
Sign up to set email alerts
|

Serous otitis media in the 20th and 21st centuries: evolving views and treatments

Abstract: The first part of the 20th century saw little change from earlier times in the recognition or treatment of SOM. Our current 21st century conceptualization and concern for SOM has come about from five advances: antibiotics, the rediscovery of the tympanostomy tube, the clinical use of middle ear impedance, the association of a history of otitis with linguistic deficiency, and recognition of the significance of transformation to a communication-based economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The outcomes of Immunoglobulin's estimation showed that OM caused increase IgG and IgM values and that can be explained by the induction of HMI, OM bacterial infections lead to rise Immunoglobulin levels due to specific Abs production especially when the infections were caused by the pathogens Staphylococcus aureus and Streptococcus pneumoniae, that was in consistent with the opinions of both [14,15].…”
Section: Discussionsupporting
confidence: 74%
“…The outcomes of Immunoglobulin's estimation showed that OM caused increase IgG and IgM values and that can be explained by the induction of HMI, OM bacterial infections lead to rise Immunoglobulin levels due to specific Abs production especially when the infections were caused by the pathogens Staphylococcus aureus and Streptococcus pneumoniae, that was in consistent with the opinions of both [14,15].…”
Section: Discussionsupporting
confidence: 74%
“…Surprisingly we found that during the time period 1925-1985, when the introduction of antibiotics completely changed the clinical picture of acute OM -and increased surgical efforts were put into the treatment of OME [8,9], the proportion of operations for OM remain stable, despite an increase both in reported OM history and surgery. Antibiotics, firstly used widespread during the second World [2], completely changed the clinical picture of ear disorders, with a reduction in mastoidectomy rates from 59% (119/ 202) to 3% (2/65) in the period 1937-1954 [3].…”
Section: Resultsmentioning
confidence: 87%
“…The virtual disappearance of the emergency cortical mastoidectomy led to an awareness and dominance of the lesser degrees of middle ear disease such as OME [2,19]. The second change during the study period was the reintroduction of ventilation tubes in 1954, leading to the increase in surgical treatment for OME [7,8,20]. The history of OME has been used as an example of how prevalence changes with diagnostic technology improvements such as otoscopy and impedance [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric auriscopes allowed better visualisation in the late 19th century and became a standard part of a general practitioner's diagnostic set in the inter-war years,22 but diagnosis by visual inspection was considered unreliable23 and remains challenging in children today. Auscultation of the ear while insufflating the Eustachian tube was also considered of value, but the diagnosis was often based on a history of hearing loss with no objective testing.…”
Section: Technological Advancementioning
confidence: 99%